Osmotic dehydration of mango with ascorbic acid impregnation: influence of process variables - Nagai, Leticia Yuri [UNESP]; Santos, Adriana Barbosa [UNESP]; Faria, Flaviana Andrade [UNESP]; Boscolo, Maurício [UNESP]; Mauro, Maria Aparecida [UNESP] (Hindawi, 2014)
The present study investigated the osmotic dehydration (OD) of mangoes cv.Palmer, dehydrated in a sucrose solution with added ascorbic acid (AA), aiming toevaluate the influence of the process variables (sucrose concentration, AA concen-tration and time) on vitamin C, water, sugars and total phenolic compound (TPC)contents by way of an analysis of the effects and the variance of the factors. Thesucrose concentration did not affect the vitamin C content, but the AA concentra-tion in the solution and the process time exerted a positive influence on thisresponse. The addition of AA also presented a significant positive effect on theTPC contents because this vitamin interferes with the quantification of the TPC.On discounting the interferences, no losses of phenolic compounds were found.Impregnation with vitamin C during OD was shown to be effective in obtainingminimally processed mangoes with high nutritional value.